Detection of human drowsiness by the vestibulo-ocular reflex compensating for heartbeat-induced head perturbations - Toshimi Yamanaka; Yutaka Hirata (Scientific Reports)
Abstract The vestibulo-ocular reflex (VOR) stabilizes vision during head movements by counter-rotating the eyes in the orbits. Although considered one of the simplest reflexes due to its minimal neuronal circuity comprising a 3-neuron arc, previous studies have shown that VOR performance deteriorates in both monkeys and humans when they are drowsy. Given constant head perturbations under dynamic environments, the VOR has been proposed as a viable biomarker for detecting human drowsiness in automobiles and other moving vehicles. However, under stationary environments where exogenous head movements are absent, its applicability has been questioned. In this study, we demonstrate that each heartbeat generates small yet distinctive head movements, and the VOR compensates for these minor head perturbations. Furthermore, we show that the effectiveness of VOR responses varies with the degree of drowsiness, indicating that the VOR can serve as an indicator of drowsiness, even in stationary contexts such as in classrooms and offices.